Flyin' solo : A nashville mystery - Peden, Peggy O'Neal (Peden, Peggy O'Neal. Nashville mystery, 2022)
"Travel agent Campbell Hale might be flying solo at her twentieth-year school reunion, but that doesn't mean she's looking for love. Her almost boyfriend, homicide detective Sam Davis, has stood her up, with the terrible excuse that he has a murder to investigate. So when she runs into her high-school sweetheart, Franklin "Fly" Young, who makes a point of telling her his marriage is in trouble, she's not interested - but she can't help but feel nostalgic. And more to the point, Fly is now a tech millionaire, and he has good news: he'd like her to take on his company's travel account. But then Campbell discovers the identity of Detective Davis' murder victim: Fly's company accountant. Was his death connected to the company, or is it a terrible coincidence? Soon Campbell is caught up in a nightmare - with her whole life on the line . . ." -- Amazon.